Correction to: Effectiveness of quality incentive payments in general practice (EQuIP-GP): a study protocol for a cluster-randomised trial of an outcomes-based funding model in Australian general practice to improve patient care - Gregory M. Peterson; Grant Russell; Jan C. Radford; Nick Zwar; Danielle Mazza; Simon Eckermann; Judy Mullan; Marijka J. Batterham; Athena Hammond; Andrew Bonney (BMC, 2019)
In the original publication of this article [1], the first name of the 3rd author is wrong.